Tick sialostatins L and L2 differentially influence dendritic cell responses to Borrelia spirochetes - Lieskovská, Jaroslava; Páleníková, Jana; Langhansová, Helena; Campos Chagas, Andrezza; Calvo, Eric; Kotsyfakis, Michalis; Kopecký, Jan (Parasites & vectors, 2015)
BACKGROUND: Transmission of pathogens by ticks is greatly supported by tick saliva released during feeding. Dendritic cells (DC) act as immunological sentinels and interconnect the innate and adaptive immune system. They control polarization of the immune response towards Th1 or Th2 phenotype. We investigated whether salivary cystatins from the hard tick Ixodes scapularis, sialostatin L (Sialo L) and sialostatin L2 (Sialo L2), influence mouse dendritic cells exposed to Borrelia burgdorferi and relevant Toll-like receptor ligands. METHODS: DCs derived from bone-marrow by GM-CSF or Flt-3 ligand, were activated with Borrelia spirochetes or TLR ligands in the presence of 3 μM Sialo L and 3 μM Sialo L2. Produced chemokines and IFN-β were measured by ELISA test. The activation of signalling pathways was tested by western blotting using specific antibodies. The maturation of DC was determined by measuring the surface expression of CD86 by flow cytometry. RESULTS: We determined the effect of cystatins on the production of chemokines in Borrelia-infected bone-marrow derived DC. The production of MIP-1α was severely suppressed by both cystatins, while IP-10 was selectively inhibited only by Sialo L2. As TLR-2 is a major receptor activated by Borrelia spirochetes, we tested whether cystatins influence signalling pathways activated by TLR-2 ligand, lipoteichoic acid (LTA). Sialo L2 and weakly Sialo L attenuated the extracellular matrix-regulated kinase (Erk1/2) pathway. The activation of phosphatidylinositol-3 kinase (PI3K)/Akt pathway and nuclear factor-κB (NF-κB) was decreased only by Sialo L2. In response to Borrelia burgdorferi, the activation of Erk1/2 was impaired by Sialo L2. Production of IFN-β was analysed in plasmacytoid DC exposed to Borrelia, TLR-7, and TLR-9 ligands. Sialo L, in contrast to Sialo L2, decreased the production of IFN-β in pDC and also impaired the maturation of these cells. CONCLUSIONS: This study shows that DC responses to Borrelia spirochetes are affected by tick cystatins. Sialo L influences the maturation of DC thus having impact on adaptive immune response. Sialo L2 affects the production of chemokines potentially engaged in the development of inflammatory response. The impact of cystatins on Borrelia growth in vivo is discussed.
Keywords: Cystatins; cystatiny; Saliva; sliny; Female; Signal Transduction; klíště; myši; kyseliny teichoové; Borrelia burgdorferi; Mice; Teichoic Acids; signální transdukce; Ixodes; zvířata; lipopolysacharidy; Mice, Inbred C57BL; Dendritic Cells; ženské pohlaví; Animals; Lipopolysaccharides; dendritické buňky; myši inbrední C57BL